Promoting Students’ Autonomous Learning through MBKM Program of Kampus Mengajar: Students’ Voice - Tuti Purwati; Slamet Riyadi; Novita Pri Andini; Laxmi Mustika Cakrawati (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The program of Merdeka Belajar Kampus Merdeka – Independent Learning, Independent Campus (MBKM) has been launched to equip the students with the skills and knowledge needed in professional settings. Kampus Mengajar, one of the programs in MBKM, allows the students to learn and contribute as teachers at schools. The study aims at evaluating the implementation of Kampus Mengajar as a part of MBKM in English Education Program at Universitas Jenderal Soedirman. The study employed both quantitative and qualitative approarch. Questionnaires and interviews were administered to the students who have joined the program of Kampus Mengajar to explore the students’ perceptions on the implementation of the program and how the program can benefit them as students majoring in English education. The result obtained from the study indicate that the implementation of Kampus Mengajar not only help and facilitate the students with the knowledge and skills needed to be teachers but also promote the concept of autonomous learning. Keywords: Kampus Mengajar, autonomous learning, perceptions